"You helped me out of that darkness" Children as dialogical partners in the collaborative post‐family therapy research interview. (19th March 2021) - Helimäki, Mira; Laitila, Aarno; Kumpulainen, Kirsti
Abstract: Applying Dialogical Methods for Investigations of Happening of Change (DIHC), this study investigated how children who had been diagnosed with an oppositional defiant or conduct disorder participated in a collaborative post‐therapy research interview and talked about their experiences of family therapy. The results showed that the children participated as dialogical partners talking in genuine, emotional, and reflective ways. Encountered as full‐membership partners, the children also co‐constructed meanings for their sensitive experiences. However, their verbal initiatives and responses appeared in very brief moments and could easily have been missed. The collaborative post‐therapy interview offered a safe forum for co‐reflection by participants on what they had found useful or difficult in the family therapy process. In this interview setting, the family first listens to reflection by the therapists on the therapy process and their thoughts on some of the family's related sensitive issues. The results indicate that when therapists present themselves as not‐knowing, receptive and accountable, therapists may facilitate reflection for all family members, including children.